Operating characteristics of the electrostatic monitors of elliptic, rectangular and circular cross-section - Ivashchenko, V.E.; Karnaukhov, I.M.; Trotsenko, V.I.; Shcherbakov, A.A. (Вопросы атомной науки и техники, 2004)
The various methods of approximation of operating characteristics of electrostatic beam position monitors were
investigated. The new method that allows on order to increase the precision of approximation of horizontal coordinate is found. The simulation of measurement of frequencies of betatron oscillations is carried out. Досліджено різні методи апроксимації робочих характеристик електростатичних датчиків положення
пучка. Знайдено новий метод, що дозволяє на порядок підвищити точність апроксимації горизонтальної
координати. Виконано моделювання вимірювання частот бетатронних коливань. Исследованы различные методы аппроксимации рабочих характеристик электростатических датчиков
положения пучка. Найден новый метод, позволяющий на порядок повысить точность аппроксимации гори-
зонтальной координаты. Выполнено моделирование измерения частот бетатронных колебаний.